State of health and physical fitness of cbf (Brazilian soccer confederation) referees from the state of espÍrito santo - da Silva, Vitor Loureiro [UNESP]; Depizzol, Carlos Eduardo do Rosário; Carletti, Luciana; Vancini, Rodrigo Luiz; Leopoldo, Ana Paula Lima; Leopoldo, André Soares (FapUNIFESP (SciELO), 2019)
Introduction: Studies indicate that the technical/tactical performance of soccer referees can be impacted by physical fitness and state of health. However, although they are routinely invited to take part in matches at national level, it is not yet clearly established whether referees who work in less prominent regions and soccer championships present the same levels of physical, technical and psychological preparation as referees from more important areas, such as the soccer teams of São Paulo and Rio de Janeiro. Within this context, no studies have evaluated the physical conditioning and health parameters of Brazilian Soccer Confederation (CBF) referees who work in Espírito Santo. Objective: To assess the health and physical fitness levels of CBF soccer referees from Espírito Santo. Methods: A cross-sectional study with 16 participants, 6 referees, and 10 assistant referees. The protocol lasted 12 weeks and consisted of the following analyses: general characteristics, body composition, flexibility, and biochemical and cardiorespiratory profiles. Results: The referees all fell under the age range (26 to 41 years) required by CBF and had good body composition and flexibility results. The cardiorespiratory assessment (rest and effort) of the referees indicated satisfactory physical fitness and consequently, low risk for cardiovascular diseases based on resting heart rate (HR) (64 ± 13 bpm), HR reserve (126 ± 18 bpm) and VO2max (45.3 ± 5.7 ml·kg-1·min-1), results similar to those seen in elite international referees. Regarding the biochemical assessment, the parameters analyzed were within the normal range. Conclusion: Despite the fact that referees from the state of Espírito Santo work in a region of lesser national significance and relevance in the soccer domain, they present satisfactory levels of physical fitness and health parameters to act with safety and precision in national competitions. Level of Evidence IV; Type of study: Case series.
Estado de salud y aptitud física de árbitros de fútbol del estado del espírito santo del cuadro de la cbf
Estado de saúde e aptidão física de árbitros de futebol do estado do espírito santo do quadro da cbf
Keywords: Effort test; Health; Physical fitness; Soccer referees